PHOW THE EDUCATIVE WORDWALL GAME AFFECTS THE INTEREST OF STUDENTS IN HIGH GRADE MATH SUBJECTS IN ELEMENTARY SCHOOL - Dinda Nuria Utami; Muhammad Hanif; Novita Larasati; Ananda Puti Gandoria; Muspiqotus Sadiyah; Inas Sadsabila; Putri Rahmawati; Ita Rustiati Ridwan; Susilawati Susilawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Mathematics is a subject that is always encountered and taught at any level an education unit. Amun, many learners view math as the most difficult subject of many subjects. This was difficult because mathematics was abstract and boring. So interest in learning the lesser lessons is highlighted with a few other subjects taught in school. So a way to leverage interest in math is to use an educational game like wordwall. The study explains how wordwall game affects the interest in elementary student mathematics and the student's interest in math. The method used in this study is to apply quantitative methods by using advanced studies in pre-test and post-test forms. The subject of this study is subulussalam elementary class v student, SDN 02 cijoro lebak, SDN new kampong researchers are taking samples of 37 students using sampling samples. Statistical data analysis results after treatment results results from sig 0,006 < 0,05 and can be drawn to the conclusion that there is a difference before treatment and after treatment. Then it can be drawn to the conclusion that between the wordwall variables has an influence with student learning interests.